2013
DOI: 10.1509/jppm.12.046
|View full text |Cite
|
Sign up to set email alerts
|

In-Group and Out-Group Influences on the Consumption Behavior of Minority Groups: The Case of Gay Men

Abstract: This article examines how and why members of a stigmatized minority group respond to in-group and out-group influences in their consumption decisions. Specifically, the authors demonstrate through a field survey that gay men are more [less] likely, compared with their straight counterparts, to conform to influences from in-group [out-group] members. Moreover, the authors show that these patterns are driven by differences across these two groups in both their horizontal and vertical collectivism values. In doin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…They feel pressured from a society that increasingly stereotypes them as simply fundamentalists. The resultant stigma (Sandikci & Ger, 2010) may force them to engage in competitive thoughts and actions towards an out-group such as multinational firms originating from non-Muslim countries (e.g., Alserhan, 2010;Hildebrand et al, 2013).…”
Section: Role Of Culturementioning
confidence: 99%
“…They feel pressured from a society that increasingly stereotypes them as simply fundamentalists. The resultant stigma (Sandikci & Ger, 2010) may force them to engage in competitive thoughts and actions towards an out-group such as multinational firms originating from non-Muslim countries (e.g., Alserhan, 2010;Hildebrand et al, 2013).…”
Section: Role Of Culturementioning
confidence: 99%
“…Furthermore, similar to Kates’ (2000, ) theorizing of brand relationships and brand legitimacy within the gay community, Hildebrand et al. () suggest that the position of in‐group status can even be extended to companies that are viewed to be gay friendly, which enables some firms and brands to earn the rank of one of us versus one of them .…”
Section: Findings and Discussionmentioning
confidence: 86%
“…These findings support Kates’ () work that suggests that some gay men who have been socialized into the gay subculture use consumption to achieve the idealized, fashionable gay social identity or as a means by which they can compensate for not attaining the rigid bodily and appearance standards—many of which are perpetuated through the images in the gay media. Hildebrand, DeMotta, Sen, and Kongsompong () looked at the role of collectivism and susceptibility to social influence and found that gay men who exhibit higher levels of collectivism are more likely to conform to in‐group (vs. out‐group) social influence in regard to consumption decisions. These findings again support the importance of the gay community and one's peers within the dynamics of gay consumer culture.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Social capital, which usually focuses on what people have (Bourdieu, 1986), can turn into social capital that focuses on what people do not have or do not use (Author, in press). This distinction can create homogeneity; protect self-esteem; and engage in perceptual, affective, and behavioral continual identity (Hildebrand, DeMotta, Sen, & Kongsompong, 2013).…”
Section: A Discursive Toolmentioning
confidence: 99%